The forearm ischaemic work test–hazardous to McArdle patients?. Issue 12 (December 1982) - Meinck, H M; Goebel, H H; Rumpf, K W; Kaiser, H; Neumann, P
Abstract : A 57-year-old patient suffering from late-onset McArdle's disease developed myoglobinaemia, massive myoglobinuria and marked serum creatine kinase elevation subsequent to a routinely performed forearm ischaemic work test. Twenty hours after the test, enhancement of 99mTc methylene-diphosphonate activity was demonstrated exclusively in the tested forearm. It is concluded that the forearm ischaemic work test is potentially hazardous to McArdle patients, as it might induce myoglobinuria sufficient to result in acute myoglobinuric renal failure.